2020
DOI: 10.3389/fnins.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal Administration of Exosome-Associated Pathological Alpha-Synuclein Is Not Sufficient by Itself to Cause Pathology Transmission

Abstract: α-Synuclein (α-syn) has been genetically and biochemically linked to the pathogenesis of Parkinson's disease (PD). There is accumulating evidence that misfolded α-syn species spread between cells in a prion-like manner and seed the aggregation of endogenous protein in the recipient cells. Exosomes have been proposed to mediate the transfer of misfolded α-syn and thus facilitate disease transmission, although the pathological mechanism remains elusive. Here, we investigated the seeding capacity of exosomeassoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…It has been reported that the aggregation propensities of mutant α-synuclein and the neurotoxicity of oligomers are related to the pathogenesis of PD [ 2 , 21 ]. Misfolded α-synuclein can be transmitted in exosomes; however, discrepancies in pathological results among different studies, due to the concentrations of exosomes injected, caused concern [ 22 , 23 ]. Monomeric α-synuclein disrupted the BBB by interacting with pericytes in patients with PD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the aggregation propensities of mutant α-synuclein and the neurotoxicity of oligomers are related to the pathogenesis of PD [ 2 , 21 ]. Misfolded α-synuclein can be transmitted in exosomes; however, discrepancies in pathological results among different studies, due to the concentrations of exosomes injected, caused concern [ 22 , 23 ]. Monomeric α-synuclein disrupted the BBB by interacting with pericytes in patients with PD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism for intercellular communication is via exosomes. Although extensive work has been done regarding the role of exosomes in neuronal aSyn transmission and disease pathology [ 366 , 579 , 580 , 581 , 582 ], few studies have proposed a vesicular-mediated transfer of neuroprotective molecules from astrocytes to neurons [ 583 , 584 ] or an exosome-related aSyn spread from neurons to astrocytes [ 585 , 586 ].…”
Section: Glia In the Cns: Scavengers Of Extracellular Asynmentioning
confidence: 99%
“…The addition of EVs isolated from WT mouse brain induces the assembly of recombinant α-syn preformed fibrils (PFFs) into higher-order multimers in vitro. In the same timeframe, no multimerization of α-syn PFF in the absence of EVs was observed [ 97 ]. However, similarly to what was described for Aβ [ 47 ], the pre-incubation of α-syn PFFs with these EVs neutralized the detrimental effects of α-syn PFFs in vitro (i.e., reduced uptake by primary cortical cultures) and in vivo (i.e., inability to induce α-syn accumulation after intrastriatal injection in WT mice) [ 97 ].…”
Section: The Role Of Evs In Pdmentioning
confidence: 99%
“…In the same timeframe, no multimerization of α-syn PFF in the absence of EVs was observed [ 97 ]. However, similarly to what was described for Aβ [ 47 ], the pre-incubation of α-syn PFFs with these EVs neutralized the detrimental effects of α-syn PFFs in vitro (i.e., reduced uptake by primary cortical cultures) and in vivo (i.e., inability to induce α-syn accumulation after intrastriatal injection in WT mice) [ 97 ]. Interestingly, the A53T α-syn mutant displays an increased association with EVs, leading to the speculation that pathogenic α-syn species may be preferentially sorted into EVs [ 90 ].…”
Section: The Role Of Evs In Pdmentioning
confidence: 99%
See 1 more Smart Citation